Personal Branding Strategy @babeheji in The New Media Era: Phenomenological Analysis in the Framework of Participatory Culture - Ulfa yuniati; Ainy Zahira Ramadhani (Jogjakarta Communication Conference (JCC), 2025)
The new media era has changed the paradigm of personal branding for content creators, where the audience is no longer a passive consumer, but an active participant in the production and distribution of content. This study uses a qualitative method by analyzing @babeheji's personal branding strategy within the framework of participatory culture. The research focuses on authenticity, content consistency, active interaction, multiplatform use, and storytelling. As a parenting content creator, @babeheji builds a digital identity that emphasizes the importance of a fatherless family. She shares daily vlogs with Eji and Momma and presents parenting education. The study found that active audience participation in various forms of digital interaction, such as comments, duet videos, and cross-platform discussions, enabled @babeheji's personal branding strategy. Increasingly decentralized and democratic content production allows audiences to be not only recipients of messages, but also partners in building digital narratives. The complexity of the narratives that emerge in the intertextual space between platforms strengthens the position of social networks over hierarchy in shaping audience engagement.Moreover, the success of personal branding in the new media era depends not only on the image built by the creator, but also on the extent to which the audience feels ownership and participates in the digital community. By understanding the dynamics of participatory culture, content creators can develop personal branding strategies that are more inclusive, interactive, and sustainable in the digital ecosystem.